Issues of Representing Time in English Literary Text - Boltaqulova Gulnoza Farruxovna (International Journal on Integrated Education, 2023)
The present article is devoted to investigation of the category of time in literary texts. In Literature, the category of time presents a certain interest in both theoretical investigation and for practical use. The purpose of this work is to examine the theories of contemporary linguists who have been working on the toping and to exhibit their thoughts and conclusions via the theme by analysing the category of time in literary texts to achieve high standards of sustainability in the world of Literature.